Improving the waiting times within a hospice breathlessness service. Issue 2 (29th May 2019) - Sime, Caroline; Milligan, Stuart; Rooney, Kevin Donal
Abstract : Background: Breathlessness, a common symptom in advanced disease, is a distressing, complex symptom that can profoundly affect the quality of one's life. Evidence suggests that specialist palliative care breathlessness intervention services can improve physical well-being, personal coping strategies and quality of life. In the UK, the use of quality improvement methods is well documented in the National Health Service. However, within the independent hospice sector there is a lack of published evidence of using such methods to improve service provision. Aim: The aim of this project was to reduce the waiting time from referral to service commencement for a hospice breathlessness service by 40%—from a median of 19.5 to 11.5 working days. Methods: Using a quality planning and systems thinking approach staff identified barriers and blockages in the current system and undertook plan-do-study-act cycles to test change ideas. The ideas tested included offering home visits to patients on long-term oxygen, using weekly team 'huddles', streamlining the internal referral process and reallocating staff resources. Results: Using quality improvement methods enabled staff to proactively engage in positive changes to improve the service provided to people living with chronic breathlessness. Offering alternatives to morning appointments; using staff time more efficiently and introducing accurate data collection enabled staff to monitor waiting times in real time. The reduction achieved in the median waiting time from referral to service commencement exceeded the project aim. Conclusions: This project demonstrates that quality improvement methodologies can be successfully used in a hospice setting to improve waiting times and meet the specific needs of people receiving specialist palliative care.